"They Hear Us But They Do Not Listen to Us": Youth Narratives on Hope and Despair in the Kurdistan Region of Iraq - Baser, Bahar (International journal of conflict and violence, 2022)
Most of the recent academic literature has focused on the macro politics of the Kurdish situation within Iraq and there is little scholarship about the younger generation of Kurds coming of age during the autonomous Kurdish rule. Unlike their forebears, they have no direct memory of the decades-long repression campaigns. For them, the history starts with the inception of a semi-autonomous Kurdish enclave and de facto self-rule after the first Gulf War in 1991. Studying ‘Generation 2000’, the Kurdish millennials who came of age in the aftermath of the United States invasion of Iraq in 2003 offers vital insights into the dynamics of a region that experienced great socio-political transformation.